Determination Of Asphaltene And C, H, N, O, S Contents In Crude Oil From X-Oilfield In South Sumatra - Tjuwati Makmur (Scientific Contributions Oil and Gas, 2009)
All analyzed crude oil samples contain firstly, the carbon contents in a range of 75.2830 % wt – 83.5739 % wt. Secondly, asphalthene with in a range of 0.6930 % wt – 1.8260 % wt and it can deposit in the formation and block the pore throats, which may reduce the permeability significantly. Thirdly, the hydrogen contents in a range of 9.1948 % wt –11.2339 % wt and it is impurities crude oil indicator. Fourthly, the crude oil samples have zero % wt nitrogen contents and don’t result in corrosive properties. However, the existence of the oxygen contents (in a range of 5.1634 % wt – 14.0560 % wt) and the sulfur contents (in a range of 0.1334 % wt – 0.2533 % wt) in the crude oil samples may cause corrosion problem.